Bergenin ameliorates cognitive deficits and neuropathological alterations in sodium azide-induced experimental dementia - Singla, Rajeev K.; Dhonchak, Konika; Sodhi, Rupinder K.; Arockia Babu, M.; Madan, Jitender; Madaan, Reecha; Kumar, Suresh; Sharma, Rohit; Shen, Bairong (Frontiers in Pharmacology, 2022)
Background: Bergenin, 4-O-methyl gallic acid glucoside, is a bioactive compound found in the cortex of Mallotus japonicus (L.f.) Müll.Arg. along with many other natural resources including that from Bergenia species. The present study delineates the neuroprotective potential of bergenin through the modulation of PPAR-γ receptors. Method: Dementia was induced in the Wistar rats by intraperitoneal (i.p.) administration of sodium azide (12.5 mg/kg for the first 5 days followed by 10 mg/kg for the next 9 days). The rats were then exposed to the Morris water maze test to assess the effect on cognitive abilities followed by a series of biochemical and histopathological evaluations. Results: Sodium azide-treated rats exhibited a severe deterioration of memory as suggested by poor performance in the spatial learning task in addition to the enhancement of brain acetylcholinesterase potential, oxidative stress, inflammation, and amyloid-β (Aβ) accumulation. Administration of bergenin to sodium azide-treated rats significantly recovered cognition and related biochemical variations. Further, co-administration of Bisphenol A diglycidyl ether (BADGE), a PPAR-γ antagonist with bergenin challenged its neuroprotective effects. Conclusions: The findings of our study exhibit that the cognitive restoration potential of bergenin may be attributed to its modulatory effects against cholinesterase, oxidative stress, and inflammatory markers, as well as its neuroprotective actions, thus aligning it as a possible therapy for Alzheimer’s disease-related dementia. The study also fortifies the significance of PPAR-γ receptors in dementia.